1986
DOI: 10.1128/mcb.6.4.1187
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of Drosophila melanogaster hsp70 cognate proteins.

Abstract: Monoclonal antibodies have been used to identify three proteins in Drosophila melanogaster that share antigenic determinants with the major heat shock proteins hsp7O and hsp68. While two of the proteins are major proteins at all developmental stages, one heat shock cognate protein, hsc7O, is especially enriched in embryos. hsc7O is shown to be the product of a previously identified gene, Hsc4. We have examined the levels of hsp7O-related proteins in adult flies and larvae during heat shock and recovery. At max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
80
0
7

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 42 publications
5
80
0
7
Order By: Relevance
“…6) appeared to be greater in the three mutant genotypes than in the Canton-S strain. This latter result supports recent data of Palter et al (22), who found that levels of Hsp7O-cognate mRNA increased twofold after exposure to heat. Presumably, a stress situation caused by a defective actin isoform could result in a comparable level of HSP-cognate protein induction.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…6) appeared to be greater in the three mutant genotypes than in the Canton-S strain. This latter result supports recent data of Palter et al (22), who found that levels of Hsp7O-cognate mRNA increased twofold after exposure to heat. Presumably, a stress situation caused by a defective actin isoform could result in a comparable level of HSP-cognate protein induction.…”
supporting
confidence: 82%
“…(27). After blocking for 1 h in 50 mM Tris (pH 7.4)-3% bovine serum albumin-0.9% NaCl-0.04% sodium azide, blots were successively incubated for 3 h with a 1:100 dilution of monoclonal antibody IPC4 (22) (18). In all three cases the mutation causing flightless phenotype maps to a chromosomal position coincident with the location of the act88F gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The HSP70 gene itself is not activated under this condition but proteins for two HSPT0 family members are induced (35). An HSP70-1ike protein is one of the first proteins synthesized after zygote formation in mouse embryogenesis (4), and several HSPs are induced during oogenesis and pupation in Drosophila (25,36,44,59,70). …”
Section: Life Cycles and Heat Shock Proteinsmentioning
confidence: 99%
“…Three of these are known only by their subunit molecular weights: HSP90, HSP70, and HSP 20-30. The precise molecular weight varies slightly among different organisms, In the eukaryotic cell, each group appears to constitute a gene family consisting of closely related protein isoforms and genes encoding sequences regulated by different promoters (14,16,19,46,50,59,79). The fourth HSP is ubiquitin, a protein of 8,000 mol wt.…”
mentioning
confidence: 99%